Tinjauan Teologis Model Pembelajaran Kooperatif Tipe TGT (Team Games Tournament) [A Theological Review of the TGT Type Cooperative Learning Model] - Gulo, Fiterianus (Universitas Pelita Harapan, 2020)
The purpose of education from Christian perspective is the effort of restoring the image of God that has been broken in human creature since human has fallen into sin. The sinful nature of human has destroyed the relationship between God and human so that human cannot understand and please God anymore. Through Christ redemption, now human has two ways to understand God, which are through general revelation and special revelation. General revelation is the world as His creation, and special revelation is His words that have been written in the Bible. Special revelation, fundamentally, is a metaphysical framework for Christians to understand God’s creation. The discovery of some education theories has given many impacts in education world. But, since human has fallen into sin, the theories become misdirection and misinterpreted. The analysis of a theory of education from Christian perspective is needed to be done so that the theory stays in God’s truth just like what God has revealed in his word. In this paper, the cooperative learning type team games tournament (TGT) is tried to be explained from theology analysis. The steps that have been done are doing the analysis presupposition og TGT, then added the theology analysis, and at the end there is a reconstruction of cooperative learning model type TGT from Christian perspective. This paper might be a reference from people who involve in Christian education to practice the cooperative learning model type TGT based on Christian values.